PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR EKONOMI PADA MATERI POKOK PASAR PERSAINGAN SEMPURNA DI KELAS X SMA NEGERI 1 SAIPAR DOLOK HOLE - Mara Judan Rambey (Jurnal Ekonomi dan Bisnis Nias Selatan, 2021)
The based of This examine is lowed lerarning outcomes of students in subject matter the market competition complete in class X SMA Negeri 1 Saipar Dolok Hole. This study aimed to examine the effect of using the problem bases learning strategies learning outcomes of students in the subject matter the market competition complete in Class X SMA Negeri 1 Saipar Dolok Hole, to looking the capability impact about the subject matter the market competition complete before and after assembling the problem bases learning strategies in class X SMA Negeri 1 Saipar Dolok Hole, to knows the which significant effect between of using the problem bases learning strategies learning outcomes of students in the subject matter the market competition completein class X SMA Negeri 1 Saipar Dolok Hole. The population in this study are all students of class X SMA Negeri 1 Saipar Dolok Hole consists of 2 classes with totaling by 52 students. The sampling technique used is random sampling technique. Thus obtained sample class X - 1 as many as 26 students. Based on calculations on statistical analysis shows that the average value of the use of the problem bases learning strategies the subject matter the market competition complete in Class X SMA Negeri 1 Saipar Dolok Hole of 2.55 with the category of "good", while the learning outcomes of students in the subject matter the market competition complete before use of the problem bases learning strategies obtained an average value of 66.34 with a category of "Enough" and after the use of the problem bases learning strategies obtained an average value of 74.23 with the category of "good / Completed". For signaling hypothesis upheld in this study received or rejected, then the inferential analysis using the formula test "t-test". From the t-test results greater than t-table (4,16 > 1.69). That means the alternative hypothesis is upheld in this study is accepted.